Kualitas Semen Beku Kuda pada Pengencer Susu Skim dengan Konsentrasi Gliserol yang Berbeda - -, Azizah; Iis Arifiantini, Raden (Jurnal Veteriner; Vol 10 No 2 (2009), 2009)
Cryoprotectant is one of determining factors for the success of stallion semen cryopreservation. Formost mammalian sperm cryopreservation,glycerol has been widely used as the cryoprotectant. Glycerol inhigh concentration is toxic to the sperm but in low concentration it has protective effect on the semen. Theobjectives of this experiment were to find appropiate glycerol concentration by using skim milk extender inorder to maintain motility and viability of spermatozoa of stallion frozen semen. Semen was collectedfrom three sexually mature stallions by using artificial vagina. The semen characteristics and qualitywere examined both macro and microscopically. Prior to extension, semen was centrifugated at 3000 rpmfor 15 minutes. The pellet was re-extended with skim milk extender with glycerol 5% (G5) 7.5% (G7.5), and10% (G10). The extended semen as then packed in mini straw (0.3ml), equilibrated at 5 oC for 2 hours,frozen in the liquid N2 vapor for15 minutes and then stored in liquid N2 container until futher evaluation.The frozen semen, was thawed at 37 oC for 30 seconds. The percentages of sperm motility and viabilitywere examihed. The result of this research showed that the sperm motility and viability in G5 was (23.8 %;35.6 %) significantly hihger (P<0.05) as compare a with G7.5 (18.1%; 28.6%) and G10. (11.8%; 23.1%). Therecovery Rate in G5 (35.4%) was significant high er (P<0.05) than G7.5 (26.9%) and G10 (17.6%). In conclusion,glicerol of 5% is recomended for cryopreservation of stallion semen extended with skim milk.
Keywords: Glycerol, frozen semen, stallion